Is Asymmetry of the Pons Associated with Hand Function and Manual Ability after Arterial Ischemic Stroke in Children? - Slavova, Nedelina; Shojai, Max Philipp; Everts, Regula; Wiest, Roland; Steinlin, Maja; Grunt, Sebastian (Neuropediatrics, 2019)
Aim This study was designed to investigate how the asymmetry of the brain stem is related to hand function and manual ability after arterial ischemic stroke (AIS) diagnosed during childhood.Method Patients diagnosed with AIS during childhood (> 5 years old, diagnosis > 2 years before recruitment) and typically developing peers were recruited by the Swiss Neuropediatric Stroke Registry. Brainstem cross-sectional areas of each side at the level of the pons were measured. Pinch and grip strength were measured with a dynamometer, quality of upper limb movement by the Melbourne Assessment 2 and manual ability by the ABILHAND-kids. An asymmetry index was calculated for all measures (except the ABILHAND-kids). Differences between groups and correlations were calculated using nonparametric statistics.Results Fourteen AIS survivors without hemiparesis, 10 AIS survivors with hemiparesis, and 47 typically developing peers were assessed. Patients with hemiparesis showed the highest brainstem asymmetry. There was a significant positive correlation between brainstem asymmetry, the asymmetry of strength and quality of upper limb movement, and a significant negative correlation between brainstem asymmetry and manual ability.Interpretation In pediatric AIS survivors, brainstem asymmetry can serve as an indirect measure of corticospinal tract integrity. It is significantly correlated with strength, quality of movement, and manual ability.
Keywords: brainstem asymmetry; arterial ischemic stroke; hemiparesis; manual ability